The Monetary Transmission Mechanism in the Tropics : A Narrative Approach - Berg, Andrew (IMF Working Papers; Working Paper ;, 2013)
Many central banks in low-income countries in Sub-Saharan Africa are modernising their monetary policy frameworks. Standard statistical procedures have had limited success in identifying the channels of monetary transmission in such countries. Here we take a narrative approach, following Romer and Romer (1989), and center on a significant tightening of monetary policy that took place in 2011 in four members of the East African Community: Kenya, Uganda, Tanzania and Rwanda. We find clear evidence of the transmission mechanism in most of the countries, and argue that deviations can be explained by differences in the policy regime in place.